Innovative design of bamboo weaving products: perspective from Hunan Province / Weiting Li, Shahriman Zainal Abidin and S’harin Mokhtar - Li, Weiting; Zainal Abidin, Shahriman; Mokhtar, S’harin (Universiti Teknologi MARA, Perak, 2024)
The development of innovative model for bamboo weaving products in Hunan is needed since there is no rules to follow that can be used as a unified point of references. The objective of this research is to investigate, to determine and to assess the innovative model for bamboo weaving products in Hunan. In term of the methodology of the studies, a variety of different literature and current models were integrated to highlight the variation in consumer responses to the visual form of the product. Through a research project employing a mixed-methods approach, work began on how crafts-people and designers elicit these responses. Interviews with craftspeople, designers and consumer surveyors played a key role in this process. The findings indicate that this model is not only replicates the previous model created for the consumer response, but also incorporates new perspectives and insights. It also provides a more comprehensive model of innovative design that places Hunan's bamboo woven products within an aesthetic framework and describes activities other than design that are important in shaping the shape of the product.